Building bridges between residents and tourism: Attitudinal support, emotional solidarity, and intentions for pro-tourism behaviours - Milene Lança; Luís Nobre Pereira; Ana Isabel Renda; Patrícia Pinto; João Filipe Marques; Célia Ramos; Manuela Guerreiro; Hio Kuan Lai (Tourism & Management Studies)
This study explores the relationships between residents' attitudes in support of tourism, emotional solidarity with tourists and willingness to engage in pro-tourism behaviours. Residents' support for tourism hinges on their perceived benefits and costs, as influenced by theories such as the Social Exchange Theory and the Theory of Reasoned Action. Despite extensive research on residents' attitudes and tourism support, pro-tourism behaviours remain underexplored. This study aims to fill this gap by investigating how residents' attitudes and emotional solidarity, including newly added indicators of interpersonal connection, impact their intentions for pro-tourism behaviours. Empirical data from a sample of 4,026 residents in the Algarve region, Portugal, were analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of this study not only offer theoretical insights but also have practical implications for destination management. These findings underscore the importance of implementing internal marketing strategies that foster a welcoming and empathetic attitude among residents towards tourists. The study's results become directly relevant and beneficial to tourism by fostering a sense of connection and appreciation for tourists among residents.